Local Cultural Curriculum Evaluation: An Anderson Model Approach - Melkior Muda Making; Widihastuti Widihastuti (Journal of General Education and Humanities, 2026)
The implementation of the Local Cultural Curriculum in Lembata Regency has not been comprehensively evaluated, despite its formal mandate under Lembata Regent Regulation No. 77 of 2022. This study aims to evaluate the implementation of the Local Cultural Curriculum of Lembata by examining the policy formulation process, curriculum implementation in instructional practice, and evaluation mechanisms at the school level using Anderson’s Evaluation Model. This research employed a qualitative case study design, using SMP Negeri 2 Nubatukan and SMP Negeri Satu Atap 92 Bean as research sites. Data were collected through in-depth interviews, classroom observations, and document analysis. Data validity was ensured through source and technique triangulation, while data analysis followed Miles and Huberman’s interactive model. The results show that the policy formulation process involved relevant stakeholders and reflected the objective of cultural preservation, although documentation of the process remains limited. Curriculum implementation has begun in schools; however, it faces challenges, including limited learning resources, uneven teacher competencies, and insufficient technical support from the local government. In addition, evaluation mechanisms have not been optimally implemented due to the absence of a structured monitoring and supervision system from the Education Office. Overall, the implementation of the Local Cultural Curriculum demonstrates initial positive progress but requires strengthened resources, systematic supervision, and continuous evaluation to achieve its cultural preservation objectives through formal education effectively.